Left-wing, democracy, and trade union insurgency in Mexico: nuclear, mining, and metallurgical workers, 1972-1985 (Revista Tempo e Argumento, 2016)
This article analyzes the history of trade union insurgency in Mexico during the 1970s and the relationship established between the left and the labor class. To do this, experiences of the Mexican National Nuclear Energy Trade Union and those of sections 11 and 147 of the mining-metallurgical trade union are analyzed. In the first case, its relationship with the democratic movement of electrical workers and the current of revolutionary nationalism are observed and in the second its links with the political organization Línea Proletaria, which has a Maoist affiliation. Both currents proposed various strategies that revived the tension existing in the Mexican labor movement in the early century, between those who thought that trade unions should not ally to political parties and instead exert direct action at work and those who advocated for political alliances, which they called multiple action. Both movements converged in the trade union movement of that period, which demanded trade union democracy and demonstrated against the austerity policy imposed by the government, as well as for the defense of natural resources. On the other hand, labor activism was manifested in an environment of greater rebelliousness combined with other social groups, a situation that ascertains advances in the struggles of workers from the industry and services, and its impact on the political, social, and cultural life in the country.